Intended College Major Choice and the Inheritance of Majors - Giorgio Brunello; Francesco Campo; Elisabetta Lodigiani; Martina Miotto; Lorenzo Rocco (Institute of Labor Economics (IZA), 2025)
Using Italian data, we study whether their intended choice of college major is affected by the college major selected by family members. We find evidence of strong inter-generational persistence, especially in medicine and health professions, followed by economics and law, and STEM. The effects are strongest for parents and less sizeable for older siblings. No effect is found for grandparents.
Keywords: I21; 330; Italy; college majors; parents